Drug Resistance Characteristics of Mycobacterium tuberculosis Isolates From Patients With Tuberculosis to 12 Antituberculous Drugs in China - Wu, Xiaocui; Yang, Jinghui; Tan, Guangkun; Liu, Haican; Liu, Yin; Guo, Yinjuan; Gao, Rongliang; Wan, Baoshan; Yu, Fangyou (Frontiers in Cellular and Infection Microbiology, 2019)
ABSTRACT Objective: To investigate the drug resistance characteristics of Mycobacterium tuberculosis (MTB) isolates from patients with tuberculosis to twelve antituberculous drugs in China. Methods: All clinical isolates of MTB were isolated from patients with tuberculosis in Shanghai Pulmonary Hospital (SPH) during the period from January 1st to December 31th, 2018. Drug susceptibility testing (DST) was performed in micro plates with 12 antituberculous drugs in accordance with relevant guideline. Demographic information, including sex, age and treatment history was recorded. Results: A total of 1950 MTB isolates were included in this retrospective study which were isolated from 1950 patients from 29 regions in China. 1644 were initial treated and 304 were re-treated in the hospital. 208 (10.67%, 208/1950) cases were diagnosed as multidrug-resistant tuberculosis (MDR-TB), from which 74 (4.50%, 74/1644) cases were initial treated, and the remaining (43.79%, 134/304) were re-treated cases. Besides, the percentage of extensively drug-resistant tuberculosis (XDR-TB) varied in such 3 different groups: 1.64% (32/1950) in total cases, 0.30% (5/1644) in initial treated cases and 8.82% (27/306) in re-treated cases. The total resistance rates were as follows: isoniazid (361, 18.51%), streptomycin (302, 15.49%), rifampin (241, 12.36%), ofloxacin (239, 12.26%), moxifloxacin (232, 11.90%), rifabutin (195, 10.00%), ethambutol (100, 5.13%), cycloserine (55, 2.82%), kanamycin (48, 2.46%), ethionamide (40, 2.05%), amikacin (39, 2.00%) and aminosalicylic acid (21, 1.08%). Rates of resistance to any drug in re-treated cases were significantly higher than in initial treated cases. The drug resistance rates of the twelve drugs were higher in males than in females. Patients older than 60 years had significantly lower percentages of MDR/XDR-TB (7.11% and 0.65%) than in younger age groups. The proportion of re-treated cases in Shanghai (11.38%, 88/373) was lower than that in other regions. Meanwhile, the percentages of MDR/XDR-TB in Shanghai (4.79% and 0.25%) were significantly lower than in other regions. Conclusions: In this study, we found higher proportion of MDR/XDR-TB among re-treated cases than initial treated cases in China and the drug resistance rate of tuberculosis varied with age, sex and region, indicating that standardized anti-tuberculosis treatment can reduce the incidence of drug-resistant tuberculosis and the recurrence of tuberculosis.